Meningkatkan Hasil Belajar Pakat Melalui Model Pbl Pada Peserta Didik Sd Negeri 6 Salaon Toba - Nurtina Pasaribu (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve the learning outcomes of Catholic Religious Education (PAKAT) through the application of the Problem-Based Learning (PBL) model among students at SD Negeri 6 Salaon Toba. The background of this research is the low learning outcomes of students in PAKAT, caused by the lack of active student engagement in the learning process and teaching methods that do not support the development of students' character competencies in line with Pancasila values. This study uses Classroom Action Research (CAR) conducted in two cycles at SD Negeri 6 Salaon Toba, with the research subjects being 14 Phase B Grade IV students, focusing on the topic "Jesus Proclaims the Kingdom of God through Parables." The research was conducted in September 2024. Data collection techniques include observation sheets, learning outcome tests, and affective observation rubrics. The research focuses not only on improving academic performance but also on developing student character in line with the Pancasila Student Profile, such as critical thinking, collaboration, independence, and faith in God Almighty. The results show that the application of the PBL model significantly improves students' learning outcomes and supports the development of the Pancasila Student Profile. In the first cycle, students' average learning outcomes increased by 10%, and in the second cycle, by 20%. Additionally, students demonstrated improvements in critical thinking, group collaboration, and responsibility in completing tasks. This study indicates that the PBL model is effective in enhancing PAKAT learning outcomes while simultaneously supporting character development in line with Pancasila values. Educators are encouraged to continue applying this learning model to integrate academic achievement and character development.